Hypertrophic varicella scars of the scalp. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
The pustular lesions of varicella can leave scars, regardless of their diameter, as shown by the variable extension of the scars themselves and, above all, independently of scratching, as shown by their distribution even in locations that are difficult to scratch. Like all scars, even those secondary to chickenpox can be atrophic, normotrophic or hypertrophic (3), rarely keloid (2). The site of the lesions influences the type of scar regardless of the type of disease. As a matter of fact, the scars of chicken pox and acne are usually atrophic on the face, while the scars of both diseases are usually hypertrophic on the trunk, especially in the upper part (1). Even on the scalp, which is the elective site of varicella lesions, the scars can be hypertrophic, as the current case shows.